Gross Measurements of the Digestive Tract and Visceral Organs of Addax Antelope (Addax nasomaculatus) Following a Concentrate or Forage Feeding Regime. (12th March 2017) - Tahas, S. A.; Martin Jurado, O.; Hammer, S.; Arif, A.; Reese, S.; Hatt, J.‐M.; Clauss, M.
Summary: Differences in macroscopic measurements of the gastrointestinal tract have been hypothesized to correlate with the browser–grazer continuum in the natural diet of ruminants. However, to what extent these characteristics represent species‐specific traits, or respond to the actually ingested diet, remains to be investigated. Twelve surplus addax antelope ( Addax nasomaculatus ) were divided into two groups and fed, for 3 months, either their usual diet, consisting of a concentrate feed with a limited amount of hay, or a diet of unlimited hay only. After culling, macroscopic measurements were compared between groups. The macroscopic anatomy of the addax showed many characteristics considered typical for grazing or 'cattle‐type' ruminants. While both diet groups had mesenteric, pericardial and perirenal adipose tissue, these depots were subjectively more pronounced in concentrate‐fed animals. Hay‐fed animals had significantly heavier filled forestomach compartments, with corresponding significantly longer linear measurements. Masseter muscles and the surface of first‐order omasal leaves were significantly more prominent in hay‐fed animals, reflecting possible adaptations to overcome resistance of grass forage and to reabsorb fluid from increased rumination, but differences were not as distinct as reported between 'cattle‐type' and 'moose‐type' ruminants. Some measurements such as reticular crests and empty foregut mass remained stable between groups, indicating possibly genetically pre‐defined characteristics less prone to change in adult life. The results emphasize the adaptability of ruminant digestive tract anatomy in adult animals even after a short period of time, but also suggest limits to this adaptability that reveals a species‐specific anatomy regardless of the diet actually consumed.